2020
DOI: 10.3390/microorganisms8081180
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Abdominal Fat Depots Reduced by Butyric Acid-Producing Leuconostoc mesenteroides

Abstract: The activation of peroxisome proliferator-activated rece ptor gamma (PPAR-γ) is known to induce the differentiation of adipocytes. This study aimed to investigate the probiotic effect of Leuconostoc mesenteroides (L. mesenteroides) on high-fat diet (HFD)-induced PPAR-γ activation and abdominal fat depots. Incubation of differentiated 3T3-L1 adipocytes with media of L. mesenteroides EH-1, a butyric acid-producing strain, significantly reduced the amounts of lipid droplets. The oral administration of L. mesenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Notably, Oscillospira exhibited lower abundance in gut of obesity and the early study involving monozygotic twins revealed a strong inverse correlation between Oscillospira and obesity ( Tims et al, 2013 ). A substantial of evidence suggested that Oscillospira played a significant role in metabolic activities related to obesity ( Gophna et al, 2017 ), while Oscillospira was capable of producing various short-chain fatty acids ( SCFAs ) dominated by butyric acid ( Gophna et al, 2017 ; Jiao et al, 2018 ) and was significantly associated with adipose and inflammatory diseases ( Konikoff and Gophna, 2016 ; Gophna et al, 2017 ; Yang et al, 2020 ). In addition, it is crucial that gut bacteria could produce large amounts of folic acid and other B vitamins for body utilize ( Morowitz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Oscillospira exhibited lower abundance in gut of obesity and the early study involving monozygotic twins revealed a strong inverse correlation between Oscillospira and obesity ( Tims et al, 2013 ). A substantial of evidence suggested that Oscillospira played a significant role in metabolic activities related to obesity ( Gophna et al, 2017 ), while Oscillospira was capable of producing various short-chain fatty acids ( SCFAs ) dominated by butyric acid ( Gophna et al, 2017 ; Jiao et al, 2018 ) and was significantly associated with adipose and inflammatory diseases ( Konikoff and Gophna, 2016 ; Gophna et al, 2017 ; Yang et al, 2020 ). In addition, it is crucial that gut bacteria could produce large amounts of folic acid and other B vitamins for body utilize ( Morowitz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several mice died during the experiment and the final sample size of each group was as follows: sham group (n = 10), CLP group (n = 10), CLP+SCFAs group (n = 12), and CLP+SCFAs+GLPG0974 group (n = 10). In the CLP+SCFAs+GLPG0974 group, SCFAs (acetate: propionate: butyrate at a ratio of 3: 1: 1) at 500 mg/kg body weight were administrated intra-gastrically two times a day for 7 consecutive days before CLP surgery, and GLPG0974 at 1 mg/kg body weight were given every 3 days for 24 days by oral gavage right before administration of SCFAs (15,20). Saline was administrated as vehicle.…”
Section: Drug Pretreatment and Experimental Designmentioning
confidence: 99%
“…Although BTI-A-404 has not been used in subsequent studies, GLPG0974 has been employed to help define roles of FFA2 in human cells and tissues [24][25][26]. Surprisingly, however, given its lack of affinity for rat and mouse FFA2, GLPG0974 has also been reported to be effective in blocking a potentially FFA2-mediated effect in rat small intestine [27] and in both a mouse model of type II diabetes [28] and the probiotic effects of Leuconostoc mesenteroide in mice [29]. Such effects of GLPG0974 in rodent models are incompatible with the known lack of affinity of this ligand at mouse and rat FFA2 and must, therefore reflect unknown 'off-target' actions of GLPG0974.…”
Section: Antagonistsmentioning
confidence: 99%